Pelaksanaan Perjanjian Pinjam Meminjam Antara Anggota Koperasi dengan Koperasi Florette di Kecamatan Langke Rembong Kabupaten Manggarai - Beatrix Meylita Ming; Siti Ramlah Usman; Petornius Damat (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the implementation of a loan and borrowing agreement between cooperative members and the Florette cooperative in Langke Rembong District, Manggarai Regency. The research was conducted with empirical research and the nature of the research was descriptive, namely researching by revealing facts objectively at the time of research in the field. The result of this research is that the implementation of a loan and borrowing agreement between cooperative members and florette cooperatives using additional collateral is a provision of collateral based on the policy pattern that applies in the Florette Cooperative. The agreement has been stated in a loan agreement letter which is made unilaterally. The reasons why members cannot fulfill their obligations are due to limited backgrounds and also external circumstances that have an impact on the income of the members. The settlement efforts from the Cooperative are carried out by means of a family approach so that both parties, namely Cooperative Members and Forette Cooperatives, are not harmed.